A new species of Imantodes Duméril, 1853 (Serpentes, Dipsadidae) from the Eastern Cordillera of Colombia - Missassi, Alexandre F. R.; Prudente, Ana L. C. (Zootaxa, 2015)
We describe a new species of Imantodes, morphologically similar to I. chocoensis, from the Eastern Cordillera of Colombia. This new species is distinguished from all congeners by the following combination of morphological characters: smooth dorsal scale rows 17/17/15; apical pits absent; infralabials 12–13; ventrals 227–236; subcaudals 147–148; presence of loreal scale; cloacal plate divided; dark temporal stripe on the suture between the lower edge of temporal scales and upper region of supralabials; dorsum of body light brown with dark brown transversal streaks, weakly evident in lateral view; hemipenis in situ extending to the level of 11th subcaudal and reaches the 10th subcaudal when everted; hemipenis with sulcus spermaticus expanded at the base of capitulum and extending distally. Additionally, we discuss the lateral expansion of the sulcus spermaticus in the new species, similar to that of species of Leptodeira.